How responding in Spanish affects CAHPS results - Floyd J. Fowler; Philip S. Brenner; Carol Cosenza; Paul D. Cleary (BMC Health Services Research, 2022)
Abstract Background The most widely used surveys for assessing patient health care experiences in the U.S. are the Consumer Assessment of Healthcare Providers and Systems (CAHPS) surveys. Studies examining the associations of language and ethnicity with responses to CAHPS surveys have yielded inconsistent findings. More research is needed to assess the effect of responding to CAHPS surveys in Spanish. Methods Subjects were patients who had received care at a study community health center in Connecticut within 6 or 12 months of being sent a CAHPS survey that asks about care experiences. The survey included four multi-item measures of care plus an overall rating of the provider. Sampled patients were mailed dual language (English and Spanish) cover letters and questionnaires. Those who did not respond after follow-up mailings were contacted by bilingual interviewers to complete the survey by telephone. We tested three hypotheses for any observed differences by ethnicity and language: 1. Spanish speakers are more likely than others to choose extreme response options. 2. The semantic meaning of the Spanish translation is not the same as the English version of the questions, resulting in Spanish speakers giving different answers because of meaning differences. 3. Spanish speakers have different expectations regarding their health care than those who answer in English. Analyses compared the answers on the survey measures for three groups: non-Hispanics answering in English, Hispanics answering in English, and Hispanics answering in Spanish. Results The overall response rate was 45%. After adjusting for differences in demographic characteristics and self-rated health, those answering in Spanish gave significantly more positive reports than the other two groups on three of the five measures, and higher than the non-Hispanic respondents on a fourth. Conclusions Those answering in Spanish gave more positive reports of their medical experiences than Hispanics and non-Hispanics answering in English. Whether these results reflect different response tendencies, different standards for care, or better care experiences is a key issue in whether CAHPS responses in Spanish need adjustment to make them comparable to responses in English.